Analisis Kinerja Layanan Cloud Computing pada Aplikasi Terabox Dengan Metode Boehm’s Quality Model - Aishka Syakirah Wibowo; Retania Dewi Anjani; Muhaimin Yahya; Ahmad Aldi Bagus (Department of Science and Technology Ibrahimy University, 2024)
Developments in gadgets/smartphones have made Terabox cloud computing storage a very popular service because it can be easily used as flexible online storage. By using the TeraBox application and using the Boehm's Quality Model method, an analysis of the Portability, Reliability, Efficiency, Human Engineering, Testability, Understandability and Modifiability metrics was carried out which was used to analyze the performance efficiency of the TeraBox cloud computing service. The research method used was an online survey with a questionnaire distributed to TeraBox users. The data collected was analyzed using a Likert scale to measure user perceptions of various aspects of TeraBox service quality. The analysis results show that TeraBox has good performance in all aspects measured, namely portability, reliability, efficiency, human engineering, testability, understandability, and modifiability. The majority of respondents have a positive perception of the TeraBox application and are satisfied with the existing service. However, this analysis also found several things that TeraBox could improve, namely more detailed information and better education on accessibility features. Overall, TeraBox is a great choice for people who need an effective and reliable cloud storage service. By implementing the suggestions above, TeraBox can increase user satisfaction and become an even better cloud computing service..